2022
DOI: 10.1088/1748-9326/ac99ef
|View full text |Cite
|
Sign up to set email alerts
|

U.S. decarbonization impacts on air quality and environmental justice

Abstract: As policy organizations consider strategies to mitigate climate change, decarbonization initiatives can also reduce health-impacting air pollutants and may affect the associated racial disparities of adverse effects. With the U.S. EPA CO-Benefits Risk Assessment Health Impacts Screening Tool (COBRA), we compare three decarbonization scenarios and their impacts at the regional and county scales. COBRA calculates changes in county-level ambient fine particulate matter (PM2.5), and associated mortality impacts, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Goforth and Nock found that without strict renewable energy and low carbon targets some electricity sector decarbonization pathways can exacerbate the pollution disparities 28 . These insights also hold beyond the electricity sectors 29 . For example, Zhu et al evaluated two decarbonization strategies (building electrification and truck electrification) in California, and found that while building electrification generates greater overall air quality benefits (~15%), it is comparatively less beneficial to disadvantaged communities 19 .…”
Section: Discussionmentioning
confidence: 89%
“…Goforth and Nock found that without strict renewable energy and low carbon targets some electricity sector decarbonization pathways can exacerbate the pollution disparities 28 . These insights also hold beyond the electricity sectors 29 . For example, Zhu et al evaluated two decarbonization strategies (building electrification and truck electrification) in California, and found that while building electrification generates greater overall air quality benefits (~15%), it is comparatively less beneficial to disadvantaged communities 19 .…”
Section: Discussionmentioning
confidence: 89%
“…Some studies suggest that past policies focused on overall emissions reductions in the electricity sector have not reduced disparities in pollutant exposure [27]. Others suggest that eliminating fossil-fuel electricity generation will have the greatest benefit for White communities, and lower benefits for communities of color [28], and that CO 2 -focused policies will not reduce racial air pollution exposure disparities [29]. However, other studies suggest that policies targeting overall air pollutant emissions reductions align well with reducing impacts to vulnerable populations [30].…”
Section: Air Quality and Health Equitymentioning
confidence: 99%
“…Recent studies have conducted this type of analysis using Chemical Transport Models (CTMs) to assess the impact of different sectors on air pollution exposure, disparities, and health. This is done by simulating emission scenarios using CTMs and assessing their impacts on population exposure. One drawback of these models is their coarse spatial resolution (typically in the order of several Kilometers), which fails to capture the large intraurban variabilities in air pollution concentrations.…”
Section: Introductionmentioning
confidence: 99%